Trinexapac-Ethyl Dose–Response Curve for Eucalyptus Growth and Hormonal Crosstalk Between Leaf and Shoot Apical Bud - Bacha, Allan Lopes [UNESP]; da Silva Santos, Renata Thaysa; de Souza Rodrigues, Juliana; Carrega, Willians César [UNESP]; Bergua, Esther Carrera; Grey, Timothy Lane; da Costa Aguiar Alves, Pedro Luís [UNESP] (Springer Nature, 2024)
Although recent studies have reported stimulatory effect of trinexapac-ethyl (TE) on eucalyptus growth, there is no consensus regarding the best dose to promote this response. Since TE acts in the gibberellin (GA) biosynthesis pathway, the study of hormonal crosstalk between the leaves and the shoot apical bud (SAB) can provide important information for understanding the positive effect previously reported. We evaluate the TE dose–response curve for eucalyptus growth in different soil moisture conditions (well watered—WW and 40% of field capacity—40-FC) and its effects on plant physiology, as well as the hormonal crosstalk between the leaves and SAB. TE caused a 49% increase in WW eucalypt growth, but not to plants under 40-FC. Estimated dose for the greatest stimulatory effect on WW eucalypt plants is 202 g a.i. ha−1. TE did not cause an increase in the plants' photosynthetic characteristics up to 15 days after application (DAA), suggesting a later increase in the eucalypt’s primary metabolism. Conversely to what have been reported for monocot crops, TE caused a fivefold increase in leaf GA1 as a short-term effect (05 DAA), but significantly decreased SAB-GA1 concentration. Leaf concentrations of indole-3-acetic acid, salicylic acid, abscisic acid and N6-isopentenyladenine also increased. TE caused changes in both 13-hydroxylated (GA20, GA1 and GA8) and non-13-hydroxylated (GA9, GA4 and GA34) GA metabolic pathways in an organ-specific manner. Our results provide information to support the use of this plant growth regulator in eucalyptus plantations, as well as insights into the hormonal crosstalk between leaves and SAB in response to TE. Graphical Abstract: (Figure presented.)
Keywords: Eucalyptus physiology; Gibberellin pathway; Plant growth regulator; Stimulatory effect